Legal Protection for Correctional Officers in Disciplinary Enforcement at Class IIB Lubuk Pakam Correctional Institutions - Gultom, Juanda; Lubis, Muhammad Ridwan; Harahap, Herlina Hanum (IHSA Institute, 2025)
Correctional officers play a critical role in maintaining order and supporting the rehabilitation of inmates within correctional institutions. Despite responsibilities comparable to other law enforcement professionals such as police officers and prosecutors, the legal protection afforded to correctional officers remains limited in practice. Although Law No. 22 of 2022, Ministerial Regulation No. 66 of 2016, and Ministerial Regulation No. 8 of 2024 provide a formal legal framework for enforcing inmate discipline and protecting officers, many officers struggle to navigate their dual role as both security enforcers and rehabilitation facilitators. This study explores the gap between legal provisions and on-the-ground realities at the Class IIB Lubuk Pakam Correctional Institutions, using a normative-empirical approach. Findings indicate that legal protection is often merely procedural and lacks meaningful institutional support. Contributing factors include overcrowded facilities, limited legal knowledge among staff, and the absence of effective deterrents against inmate violations—all of which leave officers feeling professionally and legally vulnerable. These conditions place correctional officers in a difficult position, where they must balance the enforcement of duties with concerns over potential legal consequences. The study concludes that strengthening legal education, enhancing institutional support, and revising current regulations are crucial steps toward improving the protection and effectiveness of correctional officers in their daily roles.